First‐time House Buying and Catch‐up: A Cohort Study. (9th September 2015) - Bottazzi, Renata; Crossley, Thomas F.; Wakefield, Matthew
Abstract : We investigate whether different ages of first‐time house buying lead to persistent differences in homeownership between cohorts. Our data span nearly 40 years and multiple cycles of England's volatile house prices. Ownership rates at thirty have differed substantially, with a significant negative association with prices. The persistence of differences is assessed using synthetic cohort techniques. Two methods of dealing with measurement error problems both indicate that cohorts with low ownership rates at thirty catch up almost all of the ownership gap by forty. Earlier access to homeownership may result in the ownership of slightly larger homes at around forty.